A comparison of diesel soot oxidation rates measured with two different isothermal set-ups. (January 2016) - Seher, Simone I.; Ess, Michaela N.; Bladt, Henrike; Niessner, Reinhard; Eigenberger, Gerhart; Nieken, Ulrich
Abstract: Soot aerosol particles which are emitted by incomplete combustion e.g. in diesel engines are known to have a big influence on the environment and the human health. A detailed understanding of their elimination through trapping and oxidation in diesel soot filters is therefore of great importance. Isothermal experiments of diesel soot oxidation are very advantageous for establishing detailed reaction kinetics. Nevertheless, most soot oxidation studies in the literature rely on non-isothermal burn-off experiments. In this study we present and compare two different experimental set-ups for determining isothermal soot oxidation rates. Such experiments gain importance in order to identify engine operation conditions and/or diesel fuel compositions, which produce more reactive soot, which is easier to oxidise. The first set-up, the so-called flat bed reactor (FBR), was originally developed for determining exhaust purification kinetics, using segments of exhaust monoliths with realistic through-flow under reproducible isothermal conditions. It has been adapted to study soot oxidation in segments of commercial diesel soot filters. The second set-up was originally designed for studying diesel soot oxidation in temperature programmed oxidation (TPO) experiments and requires a lower experimental effort. Although the two set-ups are very different, basic results of the oxidation experiments obtained turn out to be quite comparable, in particular under active regeneration conditions. This allows us to reduce the experimental effort by replacing some of the isothermal FBR experiments by isothermal TPO. Abstract : Highlights: Two different experimental set-ups for the isothermal soot oxidation are presented. Results of these set-ups are quite comparable. Detailed isothermal soot oxidation study with reduced experimental effort.